Heparanase-2 protein and peptides have a protective effect on experimental glomerulonephritis and diabetic nephropathy - Baranca Buijsers; Marjolein Garsen; Mark de Graaf; Marinka Bakker-van Bebber; Chunming Guo; Chunming Guo; Xue Li; Xue Li; Johan van der Vlag (Frontiers Media S.A., 2023)
Introduction: The endothelial glycocalyx degrading enzyme heparanase-1 (HPSE1) is a major contributor to kidney diseases, such as glomerulonephritis and diabetic nephropathy. Therefore, inhibition of HPSE1 could be an interesting therapeutic strategy to treat glomerular diseases. A possible HPSE1 inhibitor is heparanase-2 (HPSE2) because HPSE2 is a structural homolog of HPSE1 without enzymatic activity. The importance of HPSE2 has been recently demonstrated in HPSE2-deficient mice, since these mice developed albuminuria and died within a few months after birth. We postulate that inhibition of HPSE1 activity by HPSE2 is a promising therapeutic strategy to target albuminuria and resulting renal failure.Methods: First, we evaluated the regulation of HPSE2 expression in anti-GBM and LPS-induced glomerulonephritis, streptozotocin-induced diabetic nephropathy, and adriamycin nephropathy by qPCR and ELISA. Second, we measured the HPSE1 inhibiting capacity of HPSE2 protein and 30 different HPSE2 peptides and assessed their therapeutic potential in both experimental glomerulonephritis and diabetic nephropathy using kidney function and cortical mRNA expression of HPSE1 and cytokines as outcome parameters.Results: HPSE2 expression was downregulated under inflammatory and diabetic conditions, whereas this effect on HPSE2 expression was absent with HPSE1 inhibition and in HPSE1-deficient mice. Both HPSE2 protein and a mixture of the three most potent HPSE1 inhibitory HPSE2 peptides could prevent LPS and streptozotocin induced kidney injury.Discussion: Taken together, our data suggest a protective effect of HPSE2 in (experimental) glomerular diseases and support the therapeutic potential of HPSE2 as HPSE1 inhibitor in glomerular diseases.